2021
DOI: 10.1007/s10606-021-09398-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Paradoxes in Decolonising HCI: A Critical Discussion

Abstract: The preponderance of Western methods, practices, standards, and classifications in the manner in which new technology-related knowledge is created and globalised has led to calls for more inclusive approaches to design. A decolonisation project is concerned with how researchers might contribute to dismantling and re-envisioning existing power relations, resisting past biases, and balancing Western heavy influences in technology design by foregrounding the authentic voices of the indigenous people in the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 106 publications
1
33
0
Order By: Relevance
“…We also invite more innovative approaches to engaging with families that are the least intrusive, participatory, and navigate the social concerns particular to Arab Muslim cultures. This is in line with current global trends in human-centered interaction research that advocate for a more inclusive approach to design and the call for decolonization of the applied participatory research methods [40,44,45].…”
Section: Call For Decolonizing Research Methods In Aging and Human-co...supporting
confidence: 76%
See 1 more Smart Citation
“…We also invite more innovative approaches to engaging with families that are the least intrusive, participatory, and navigate the social concerns particular to Arab Muslim cultures. This is in line with current global trends in human-centered interaction research that advocate for a more inclusive approach to design and the call for decolonization of the applied participatory research methods [40,44,45].…”
Section: Call For Decolonizing Research Methods In Aging and Human-co...supporting
confidence: 76%
“…By 'decolonizing' research methods, we aim to promote the necessity of serious consideration of the interplay between who, where, to whom, and how research methods or approaches are not developed or adapted to the target end users or research participants. Previous research has shown that research methods in aging and HCI are not culturally universal, and that it is necessary to adapt methods or even develop new methods when conducting fieldwork with older persons in the Arab region [9,40].…”
Section: Call For Decolonizing Research Methods In Aging and Human-co...mentioning
confidence: 99%
“…Guidance for the former is set in a variety of local, national and other structures, and includes so-called traditional structures. However, language dominance and enshrined Eurocentric institutionalisation, social practices and philosophies on practices, especially in the sciences, obscure Southern voices 9 , 139 .…”
Section: Discussionmentioning
confidence: 99%
“…This not only espouses mobility and connectedness as the defining characteristics of our world and its societies but currently also lacks any significant learning dimension [73,74]. Other kindred and complementary communities are those advocates of critical pedagogies with digital interests [75,76], and researchers in the m4d, ICT4D [77] and HCI4D communities [78,79] with interests in learning and decolonisation [80,81], perhaps decolonising the curriculum, perhaps decolonising research methods. This resonates with our desire to see a mobile learning paradigm that makes no Eurocentric or Northern assumptions, and recognises the unique and universal place of mobile digital technologies, a counterbalance to the schools, state education systems and scaled corporate digital learning that are the strongholds of the established 'mobile learning' paradigm.…”
Section: Results: a New Paradigm-mobile Learning20mentioning
confidence: 99%